Isolation of indigenous enteroviruses from chemically treated and dewatered sludge samples. - Goddard, M R (1982)
Samples of wastewater sludge were examined for infectious enteroviruses before and after they had been chemically conditioned and dewatered. The least virus was recovered from the cake produced by filter pressing of sludge, which had a greatly increased solids content (39 to 45% [wt/vol]) relative to the untreated sludge (4.2 to 6.2% [wt/vol]) and in one plant was at pH 11 due to the lime conditioner used. Conditioning with a cationic polyelectrolyte before dewatering by centrifugation produced a watery sludge (2.7 to 5.3% [wt/vol]) from which high titers of infectious virus were recovered which were often greater than those isolated from the untreated sludge (0.6 to 1.4% [wt/vol]). This was thought to be due to saturation of virus and sludge floc adsorption sites by the polyelectrolyte, resulting in the liberation of virions from the sludge solids.